Functional data analysis of the power-duration relationship in cyclists - Puchowicz, M. J.; Skiba, P. F. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To extract, prioritize, and model the highly conserved variations in mean-maximal power (MMP) data in cyclists utilizing functional principal component (FPC) analysis.